A within-subject analysis of other-regarding preferences - Mariana Blanco; Dirk Engelmann; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
We assess the predictive power of a model of other-regarding preferences - inequality aversion - using a within-subjects design. We run four different experiments (ultimatum game, dictator game, sequential-move prisoners' dilemma and public-good game) with the same sample of subjects. We elicit two parameters of inequality aversion to test several hypotheses across games. We find that within-subject tests can differ markedly from aggregate-level analyses. Inequality-aversion has predictive power at the aggregate level but performs less well at the individual level. The model seems to capture various behavioral motives in different games but the correlation of these motives is low within subjects.
Keywords: C72; C91; 330; behavioral economics; experimental economics; inequality aversion; otherregarding preferences; Verhaltensökonomik; Soziale Beziehungen; Präferenztheorie; Gerechtigkeit; Test